THE ROLE OF THE DEMOCRATIC PARTY IN FOUNDING THE "ASOCIACIÓN OBRERA DE FOOT-BALL DE SANTIAGO". FROM WORKER SOCIABILITY TO INSTRUMENTAL FRIENDSHIP (CHILE. 1903 - 1907) - Villarroel, Francisco Javier (Revista de Historia Social y de las Mentalidades, 2024)
In the context of transformations of the forms of popular struggle and of the politicization of the workers’ sectors of the end of the 19th century and beginning of the 20th century.XX, and through the concepts of workers’ sociability and instrumental friendship and the analysis and contents of the workers’ press of the democratic party, we examine the ideological trajectory of the football workers’ clubs and how the doctrinal sector of the democratic party, what are the benefits that each one delivers for the other, and analyze how the foundation of the Football Workers’ Association implies a politicization of a particular way of practicing football by the verification of the new networks of influence that they generate together, new forms of support among workers and participation in activities of the democratic party